2016
DOI: 10.1186/s40854-016-0024-y
|View full text |Cite
|
Sign up to set email alerts
|

Causality between bank’s major activities and economic growth: evidences from Pakistan

Abstract: Background: Banking is an important sector of Pakistan's economy. It is general consideration that bank's major activities saving and lending have positive impact on economic growth. So the aim of this study is to investigate this consideration and also investigate that either growth led deposits and credits, or deposit and credits led growth means the purpose of this study is to investigate the direction of this relationship. Methods: Johansen test of Co-integration and Granger Causality is employed by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Bsenberg S(2018) In order to study the impact of capital tax on macroeconomic output, it makes an empirical analysis based on the data samples of 79 countries from 1996 to 2011 and exogenous growth model, it is found that reducing capital tax has a positive impact on output [11]. Mushtaq(2016) Based on the time series data of Pakistan from 1961 to 2013, it is found that there is no Granger causality between the banking savings & lending business and the economic growth in the long term and short term through cointegration test and Granger causality test, but the economic growth affects the bank's lending business, so the lending procedures should be simplified during the peak period of economic growth. [12].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Bsenberg S(2018) In order to study the impact of capital tax on macroeconomic output, it makes an empirical analysis based on the data samples of 79 countries from 1996 to 2011 and exogenous growth model, it is found that reducing capital tax has a positive impact on output [11]. Mushtaq(2016) Based on the time series data of Pakistan from 1961 to 2013, it is found that there is no Granger causality between the banking savings & lending business and the economic growth in the long term and short term through cointegration test and Granger causality test, but the economic growth affects the bank's lending business, so the lending procedures should be simplified during the peak period of economic growth. [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mushtaq(2016) Based on the time series data of Pakistan from 1961 to 2013, it is found that there is no Granger causality between the banking savings & lending business and the economic growth in the long term and short term through cointegration test and Granger causality test, but the economic growth affects the bank's lending business, so the lending procedures should be simplified during the peak period of economic growth. [12]. Chen S W(2018) studies the causality between energy consumption and economic growth of 29 provinces in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Panel regression analysis results revealed that the developments in credit activities had a crucial impact on the level of national income. Mushtaq (2016) explicated the association between bank credits and economic growth for the Pakistani economy between 1961-2013. Johansen Cointegration and Granger Causality Test results asserted that economic development had a significant influence on the demand for bank credits.…”
Section: Kaplanmentioning
confidence: 99%
“…On the other hand, numerous empirical research studies have determined unidirectional causality from the direction of economic growth towards the credits approved by commercial banks. In connection with that, the leading influence of economic growth on banks' credit activity was established in Palestine (Awad & Al Karaki, 2019), Russia (Ono, 2017), Pakistan (Mushtaq, 2016) and China (Liang & Teng, 2006), whereas the bidirectional causal relationship was detected in Poland (Škare et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%